An Assessment of the First Round Impact of Innovation Industries on Europe's Regional Economies - Adrian Otoiu; Ramona Bere; Cătălin Silvestru (Amfiteatru Economic Journal, 2017)
This paper attempts to give an economic perspective of the impact of the innovation industries. The estimation method used is that of panel data modelling, based on data from regions from European countries, including countries from Central and Eastern Europe, for which exploratory analysis was conducted on the effects of employment counts, number of companies, and wages per capita, in computer and related activities and research and development industries. Higher employment in both industries have positive effects on total employment and GDP/Capita. No sizable displaced workers effects can be seen, as higher employment and wages/capita in innovation industries are accompanied by higher employment and lower unemployment at regional level. Positive effects can be observed for both young and mature workers, and are stronger for the latter, pointing out to strong potential spillover effects. Number of local companies is not a relevant indicator for assessing the influence of research and development activities. All these effects point to the sustainability of innovation industries, which not only lead to increase of GDP per capita, but also show positive spillover effects, increase employment and reduce unemployment. The results for countries from Central and Eastern Europe (CEE) have been to some extent less significant, due to several objective factors. The results should also be viewed in the framework of the transition and catch-up period that characterizes the evolution of the CEE economies. The positive effects of strong growth are primarily reflected in GDP growth, and it may be that it takes a while for these effects to propagate in the rest of the economy in terms of job creation and sizable reduction of unemployment. While the current analysis revealed some of the first-round impacts of the innovation industries, much work remains to be done in matching these effects with other determinants of employment and unemployment, which can improve existing models with relevant empirical elements.
Keywords: R11; R23; O32; L86; 330; regional growth; innovation; research and development; computer and related industries; labour market; employment; unemployment